Prevalence and Seroincidence of Hepatitis B and Hepatitis C Infection in High Risk People Who Inject Drugs in China and Thailand. (27th March 2014) - Jackson, J. Brooks; Wei, Liu; Liping, Fu; Aramrattana, Apinun; Celentano, David D.; Walshe, Louise; Xing, Yi; Richardson, Paul; Jun, Ma; Beauchamp, Geetha; Donnell, Deborah; Ruan, Yuhua; et al.
Abstract : We determined the prevalence and incidence of HBV and HCV infection in people who inject drugs (PWIDs) at high risk for HIV in China and Thailand and determined the association of HBV and HCV incidence with urine opiate test results and with short-term versus long-term buprenorphine-naloxone (B-N) treatment use in a randomized clinical trial (HPTN 058). 13.8% of 1049 PWIDs in China and 13.9% of 201 PWIDs in Thailand were HBsAg positive at baseline. Among HBsAg negative participants, the HBsAg incidence rate was 2.7/100 person years in China and 0/100 person years in Thailand. 81.9% of 1049 PWIDs in China and 59.7% of 201 in Thailand were HCV antibody positive at baseline. The HCV confirmed seroincidence rate among HCV antibody negative PWIDs was 22/100 person years in China and 4.6/100 person years in Thailand. Incident HBsAg was not significantly different in the short-term versus long-term B-N arm in China or Thailand. Participants with positive opiate results in at least 75% of their urines during the time period were at increased risk of incident HBsAg (HR = 5.22; 95% CI, 1.08 to 25.22;P = 0.04 ) in China, but not incident HCV conversion in China or Thailand.